Oxytocin Receptor Gene Associated with the Efficiency of Social Auditory Processing - Tops, Mattie; Van IJzendoorn, Marinus H.; Riem, Madelon M.; Boksem, Maarten A.; Bakermans-Kranenburg, Marian J. (Frontiers in Psychiatry, 2011)
Oxytocin has been shown to facilitate social aspects of sensory processing, thereby enhancing social communicative behaviors and empathy. Here we report that compared to the AA/AG genotypes, the presumably more efficient GG genotype of an oxytocin receptor gene polymorphism (OXTR rs53576) that has previously been associated with increased sensitivity of social processing is related to less self-reported difficulty in hearing and understanding people when there is background noise. The present result extends associations between oxytocin and social processing to the auditory and vocal domain. We discuss the relevance of our findings for autistic spectrum disorders (ASD), as ASD seems related to specific impairments in the orienting to, and selection of speech sounds from background noise, and some social processing impairments in patients with ASD have been found responsive to oxytocin treatment.